Clinical epidemiology and treatment patterns of patients with multicentric Castleman disease: results from two US treatment centres. (6th January 2014) - Robinson, Don; Reynolds, Matthew; Casper, Corey; Dispenzieri, Angela; Vermeulen, Jessica; Payne, Krista; Schramm, Judy; Ristow, Kay; Desrosiers, Marie‐Pierre; Yeomans, Karen; Teltsch, Dana; Swain, Richard; et al.
Summary Multicentric Castleman disease (MCD) is a rare lymphoproliferative disease with little known about its epidemiology or treatment modalities. Clinical and demographic data of MCD patients identified between 2000 and 2009 were collected from medical records at two United States (US) MCD referral centres. ZIP codes identified patient residences; prevalence and incidence were estimated based on catchment areas. Patient clinical, demographic, and biochemical characteristics, drug therapies and medical utilization were descriptively reported. MCD patients (n = 59) were 61% male, mean age of 53 years (median = 55 years) and 68% Caucasian. Of those with known human immunodeficiency virus (HIV) status (n = 41), 85% (n = 35) were negative, 15% (n = 6) were positive. Most frequent physician‐reported symptoms (n = 33) were fatigue (49%, n = 16), fever (39%, n = 13), and night sweats (30%, n = 10). The estimated US 10‐year prevalence was 2·4 per million. During first year of follow‐up after study entry, the top two systemic therapies (n = 27) were monotherapies: prednisone (33%, n = 9) and rituximab (19%, n = 5). After a follow‐up of 2 years, 92% of patients were alive. This study provides new information on MCD population demographics, treatment patterns, and medical utilization; a minimal US period prevalence rate is proposed. Study replication is needed to improve external validity.